Portuguese fish producers' organisations. Some concerns - Dias, João Ferreira (2008)
An overview of the Portuguese Fish Producers' Organisations and the presentation of the main results of a survey answered by their members. The logic of the "Mutual Coercion" agreeded upon the Producers' Organisations members.